The Critical Axial Force Model in Drilling of Carbon Fiber Reinforced Composites under Different Stacking Modes. (January 2019) - Li, M; Tian, W; Sun, H L; Liu, Z; Zhang, L; Liao, W H; Hua, F F
Abstract: Delamination is a failure mode in which the initial crack propagates along the interlayer due to the axial force pushing the uncut material beyond the interlaminar shear strength during drilling. Therefore, it is necessary to study the effect of axial force on the delamination of carbon fiber reinforced composites (CFRP) during drilling. The critical axial force model of different stacking modes is established based on linear elastic fracture mechanics, thin plate bending theory, composite mechanics and superposition principle. The experimental results show that the theoretical values are in good agreement with the experimental values and can be used to predict the critical axial force to suppress the formation of delamination defects.